If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2a = 66 Reorder the terms: 2a + 5x = 66 Solving 2a + 5x = 66 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5x' to each side of the equation. 2a + 5x + -5x = 66 + -5x Combine like terms: 5x + -5x = 0 2a + 0 = 66 + -5x 2a = 66 + -5x Divide each side by '2'. a = 33 + -2.5x Simplifying a = 33 + -2.5x
| 35x+(-185)=750-50x | | 6a^2+16a-70=0 | | q+404=882 | | 4.04x+8.08=16.16 | | 5(x+8)-3(x+8)=4(x+8)-3x | | 5*a=60 | | 3x=196 | | -4+c=24 | | 0.33+1.66=9.99 | | (3x-1)/2=2/3 | | -11+2x=4x+17 | | (7/10y^2)(-2y^3)(3y^2) | | -3+6y=6y | | -192+2x=11x+78 | | -15a^2+34a-15=0 | | 3d=6+3d | | -2-x=-17 | | 110=36/x | | 5x-80=180 | | 12r^2+5ry-25y^2=0 | | 10r=7+9r | | 5x-10=2-2x+10-30 | | 8v=-7+9v | | 7(34x+23)=17(28-x) | | 20a^2-49ab+30b^2=0 | | 14x=45x+3 | | 4-1/x=3/x2 | | 6(2n-3)=13n+18 | | 3.78= | | 2h+7=3h | | 4a+24=84 | | 5s=5s+4 |